2000
DOI: 10.1038/sj.onc.1203339
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: E6 proteins from diverse cutaneous HPV types inhibit apoptosis in response to UV damage

Abstract: In addition to their role in anogenital cancer, human papillomaviruses (HPVs) are also involved in the development of a range of cutaneous lesions. HPV types 5 and 8 are associated with the development of skin cancers in individuals with Epidermodysplasia verruciformis (EV). A broad spectrum of HPV types are also commonly found in non-melanoma skin cancers in immunocompromised individuals, such as organ transplant recipients. The skin cancers in EV and immunocompromised patients occur predominantly at body sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(140 citation statements)
references
References 39 publications
5
132
1
2
Order By: Relevance
“…Although cutaneous HPV E6 can promote Bak proteolysis in human keratinocytes, the cells used in these experiments are not the natural host for the virus, however, previous studies have shown that the ability of E6 to target the apoptotic machinery is not dependent upon cell type or p53 status. 7,27 Mutations in HPV5 E6 can influence target specificity…”
Section: Identification Of Regions Of Hpv5 E6 Involved In Bak Degradamentioning
confidence: 99%
“…Although cutaneous HPV E6 can promote Bak proteolysis in human keratinocytes, the cells used in these experiments are not the natural host for the virus, however, previous studies have shown that the ability of E6 to target the apoptotic machinery is not dependent upon cell type or p53 status. 7,27 Mutations in HPV5 E6 can influence target specificity…”
Section: Identification Of Regions Of Hpv5 E6 Involved In Bak Degradamentioning
confidence: 99%
“…Having previously demonstrated that HPV E6 interferes with UVB-induced apoptosis in a number of different cell types, we were interested to investigate the consequences on the mitochondrial apoptotic pathway [20,28]. HT1080 cells that express UV-inducible Bak and p53 were transfected with the HPV E6 gene of HPV types 5, a β-papillomavirus found in NMSC, and HPV 18, a mucosal HPV found in anogenital cancers [29].…”
Section: Hpv E6 Inhibits Uv-induced Mitochondrial Morphological Changmentioning
confidence: 99%
“…The main risk factors for cutaneous SCC are prolonged sun exposure and pigmentation grade of the skin. Interestingly, several studies have revealed diverse interactions of persisting betapapillomaviruses and UV irradiation, which may be relevant to the multi-step process of skin carcinogenesis (Akgül et al, 2005;Giampieri & Storey, 2004;Jackson & Storey, 2000;Jackson et al, 2002;Underbrink et al, 2008). We therefore evaluated the synergistic effects of UV light in transgenic animals.…”
Section: Introductionmentioning
confidence: 99%